Interferometry computation of advanced land observing satellite (ALOS-2) data for the northern Ecuador Region - Goyes Gordon, Jhon Manuel (2022)
Ecuador has several seismicity sources, including the Nazca – South America megathrust in the west, the Interandean Fault System (IFS) between the Cordilleras Occidental and Real, and an active back-arc fold and thrust belt in the East. The surface deformation associated with the subduction megathrust has been well constrained in prior studies, but this is not the case for the other two systems, representing a significant gap in the characterization of seismic hazards. The IFS runs directly under or close to several major cities, including Quito, Riobamba, and Ibarra. Earthquakes have destroyed all these cities in the past. Near Quito, the IFS has a fault called the Quito Fault, which is a thrust fault that underlies and uplifts the city. This study performs Interferometric Synthetic Aperture Radar (InSAR). InSAR is a tool to characterize the deformation caused by different sources, including faults and landslides using Synthetic Aperture Radar (SAR) images. The processing used in this project will use 280 Sentinel-1 images taken over the area of Quito and the valleys to its east. Then, we use time-series analysis to obtain deformation rates. Moreover, we addressed the main methodological aspects of the processing steps and their implications. The processing of the data collected of Sentinel-1 is an expensive task, so we need to use a High-Performance Computing (HPC) system and different computational techniques for spaceborne geodetic data to process all the data collected in this project. In general, our results contribute to having a better understanding of seismic hazards in Ecuador. The overarching goal of this work is to develop a deformation map constructed by the deformation caused by the Quito Fault and other sources.